Dreamweaver MX Developer Certification Study Guide - Campbell, Marc (McGraw-Hill, 2011)
This is a complete classroom-based study guide covering Macromedia's Dreamweaver Developer certification. it includes an example site that incorporates all the features and concepts that are discussed.